Coaching and Coach Education in Russia: Ice Hockey - Bespomoshchnov, V. A.; Mikhno, L. V. (International Sport Coaching Journal, 2017)
The purpose of article is to provide an overview of coaching and coach education in Russia with a focus on ice hockey coaching. The coach education system in Russia is in a transitional stage. Previously, it was a threestage model: Baccalaureate Degree, Specialist Degree and Master`s Degree in any sport (Mikhno, Vinokurov, & Maryanovich, 2004). However, a law created by The Ministry of Sport (2014) delegated the establishment of a coaching certification system to each of the sports federations. The Russian Ice Hockey Federation (RIHF) proposed a 4-level license system. The N.G. Puchkov`s Ice Hockey Coaching Academy is the modern school for ice hockey coaches, which has evolved from Tarasov`s Higher Education School for Ice Hockey Coaches. Anatoly Tarasov is the Russian ice hockey coach who developed the system in the 1920s when ice hockey was first introduced to the USSR. Ice hockey coach education in Russia is gradually developing every year.